2015
DOI: 10.1063/1.4936836
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wide acoustic band gaps in pillar-based phononic crystal strips

Abstract: An original approach for designing a one dimensional phononic crystal strip with an ultra-wide band gap is presented. The strip consists of periodic pillars erected on a tailored beam, enabling the generation of a band gap that is due to both Bragg scattering and local resonances. The optimized combination of both effects results in the lowering and the widening of the main band gap, ultimately leading to a gap-to-midgap ratio of 138%. The design method used to improve the band gap width is based on the flatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…The reported data refer to three-dimensional or two-dimensional (in-plane waves) configurations of continuous (bold lines) or cellular (dashed lines) structures. The band-gap widths have been re-calculated for a unit cell size of 10mm, based on the data provided in the original works [17][18][19][20][21]35], for a uniform comparison.…”
Section: Dispersion Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The reported data refer to three-dimensional or two-dimensional (in-plane waves) configurations of continuous (bold lines) or cellular (dashed lines) structures. The band-gap widths have been re-calculated for a unit cell size of 10mm, based on the data provided in the original works [17][18][19][20][21]35], for a uniform comparison.…”
Section: Dispersion Analysismentioning
confidence: 99%
“…The unit cell size is h uc =10 mm and the material volume fraction V m are indicated for each structure. The initial data are taken from [17] for coated Au circles in epoxy; [21] for convex and concave holes in copper; [35] for cross-like holes in a polymer; [20] for polymeric spheres joined by ligaments; [19] for Tg scatterers in epoxy; [18] for Si strip with Tg pillars. + + versus frequency f for an accordion-like meta-chain (30 unit cells).…”
Section: Band-gap Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Assouar and Oudich [18] reported that, by using double-sided stubbed phononic plates, locally resonant band gaps could be enlarged. Coffy et al [19] designed a strip consisting of periodic pillars deposited on a tailed beam, enabling the generation of an ultra-wide band gap resulting from both Bragg scattering and local resonance. Midtvedt et al [20] considered a graphene membrane that is deposited on top of a square lattice of cylindrical pillars to exhibit coupled localized modes with nonlinear dynamics.…”
Section: Introductionmentioning
confidence: 99%